Effects of Resistant Starch Supplementation on Metabolic Parameters and Oxidative Stress in C57BL/6 Mice Fed With a High-Fat Diet - Héric Holland; Priscila Nogueira Bezan; Bárbara Ferreira Vercesi; Paula Payão Ovídio; Leandra Náira Zambelli Ramalho; Alceu Afonso Jordão (Advanced Gut & Microbiome Research)
Resistant starch is a type of dietary fiber with prebiotic properties, potential action on intestinal permeability, and an effect on decreasing glycemic levels, presenting therapeutic potential for issues stemming from excess body fat and associated comorbidities, such as nonalcoholic fatty liver disease (NAFLD). Sixty C57BL/6 mice were allocated to the following diets for 4 months: control (C), normolipid rich in fiber (F), normolipid supplemented with resistant starch (RS), high fat (HL), HL rich in fiber (HLF), and HL supplemented with resistant starch (HLRS). The following parameters were analyzed: animal weight, body composition, food intake, fasting blood glucose, lipid profile, hepatic and intestinal histology, hepatic and intestinal oxidative stress, and assessment of short-chain fatty acids in feces. Long-term supplementation with high doses of resistant starch effectively reduced body weight gain and decreased liver and retroperitoneal adipose tissue weights, blood glucose levels, alanine aminotransferase, and serum triglycerides. Intestinal histology showed that the high-fat diet increased the total diameter of the intestinal lumen (846.81±7.82) and reduced enteric muscle thickness (8.51±0.51), while resistant starch supplementation effectively improved these parameters (658.01±3.82; 30.56±0.66), also increased butyrate production, and reduced oxidative stress in the intestine. Resistant starch supplementation was effective in reducing weight, adiposity, and NAFLD in mice with diet-induced obesity and metabolic syndrome (MS).